2017
DOI: 10.1037/dev0000238
|View full text |Cite
|
Sign up to set email alerts
|

Moderate baseline vagal tone predicts greater prosociality in children.

Abstract: Vagal tone is widely believed to be an important physiological aspect of emotion regulation and associated positive behaviors. However, there is inconsistent evidence for relations between children’s baseline vagal tone and their helpful or prosocial responses to others (Hastings & Miller, 2014). Recent work in adults suggests a quadratic association (inverted U-shape curve) between baseline vagal tone and prosociality (Kogan et al., 2014). The present research examined whether this nonlinear association was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
85
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 75 publications
13
85
6
Order By: Relevance
“…Broadly, our research supports that resting RSA is quadratically related to prosociality. However, in contrast to Miller et al (), who found this association in a low‐risk sample of 3‐ to 4‐year‐olds, we did not find consistent relations between resting RSA and prosociality in our sample of 4‐year‐olds. One potential explanation for these divergent findings is that the Miller et al () study used observed behavior in lab‐based tasks to assess situation‐specific prosociality in their low‐risk sample of children.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Broadly, our research supports that resting RSA is quadratically related to prosociality. However, in contrast to Miller et al (), who found this association in a low‐risk sample of 3‐ to 4‐year‐olds, we did not find consistent relations between resting RSA and prosociality in our sample of 4‐year‐olds. One potential explanation for these divergent findings is that the Miller et al () study used observed behavior in lab‐based tasks to assess situation‐specific prosociality in their low‐risk sample of children.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to Miller et al (), who found this association in a low‐risk sample of 3‐ to 4‐year‐olds, we did not find consistent relations between resting RSA and prosociality in our sample of 4‐year‐olds. One potential explanation for these divergent findings is that the Miller et al () study used observed behavior in lab‐based tasks to assess situation‐specific prosociality in their low‐risk sample of children. We used dispositional child and caregiver reports that asked how the child generally acts and feels, and the associations between state and dispositional measures can be weak in childhood (e.g., Zuffiano, Sette, Colasante, Buchmann, & Malti, ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The obtained results supported prior assertions that (a) parasympathetic reactivity may be more relevant for understanding prosocial behavior than sympathetic reactivity (Porges, 1995(Porges, , 2007, (b) the nature of these relations may be nonlinear (Kogan et al, 2014;Miller et al, 2017), and (c) empathy-inducing stimuli, such as sadness, may be more relevant than other emotion contexts for understanding prosocial development (Eisenberg, 2010;Eisenberg & Fabes, 1990). The obtained results supported prior assertions that (a) parasympathetic reactivity may be more relevant for understanding prosocial behavior than sympathetic reactivity (Porges, 1995(Porges, , 2007, (b) the nature of these relations may be nonlinear (Kogan et al, 2014;Miller et al, 2017), and (c) empathy-inducing stimuli, such as sadness, may be more relevant than other emotion contexts for understanding prosocial development (Eisenberg, 2010;Eisenberg & Fabes, 1990).…”
Section: Strengths and Limitationssupporting
confidence: 87%